Linoleic acid: have we understood how it works in psychopathologies and Ischemic Cardiovascular Diseases? - Cocchi, Massimo; Mondo, Elisabetta; Minuto, Chara; Lercker, Giovanni (Progress in Nutrition, 2020)
The question about Linoleic Acid, which remains arguable, is whether the Linoleic Acid is inversely correlated to the Cardiovascular Disease or not and whether increasing the intake over the Recommended Daily Allowance (RDA) is positive or negative. The scientific literature, past and recent, is still controversial about the matter. To try to answer this controversy, it is important to remember the role of the Linoleic Acid in the membrane and its relationship with cholesterol. Furthermore, it is important to examine the effect of the oxidation of Linoleic Acid, its impact on the gut microbiota and the consequences on the gut epithelial integrity. Highlights. Nutritional considerations about Linoleic Acid > Characteristic of oxidizability of Linoleic Acid with respect to the cell membrane function > Linoleic Acid in platelets > The position of Linoleic Acid with respect to Psychopathology and Ischemic Cardiovascular Disease > Linoleic Acid and its effect on gut bacteria adhesion to gut epithelial barrier.